Evaluation of Donor and Recipient Characteristics Involved in Descemet Stripping Automated Endothelial Keratoplasty Outcomes - Lanza, Michele; Boccia, Rosa; Ruggiero, Adriano; Melillo, Paolo; Bifani Sconocchia, Mario; Simonelli, Francesca; Sbordone, Sandro (Frontiers in Medicine, 2021)
Aims: to evaluate both donor and recipient features involved in visual acuity restoring and complication insurgence in eyes that have undergone Descemet stripping automated endothelial keratoplasty (DSAEK). Methods: in this retrospective study, charts of 111 eyes of 96 patients (mean age 70.25 ± 8.58 years) that underwent DSAEK were evaluated. Only Fuch’s Distrophy (FD) or Bullous Keratopathy (BK) due to cataract surgery eyes were included. A complete ophthalmic check with endothelial cell density (ECD) and central corneal thickness (CCT) measurement was performed before surgery and at 1, 3, 6 and 12 months follow-up. Each DSAEK was performed by the same well-trained surgeon; only precut lenticules, provided by same Eye Bank, were implanted. Results: A total of 48 (43%) complications have been observed (most of them were 22 partial graft detachments and 17 IOP spikes). At the last follow-up (mean: 8,58 ± 4,09 months), a significant increase (p<0.05) of best corrected visual acuity (BCVA) was detected. Overall mean BCVA of the eyes evaluated was 0,40 ± 0,43 LogMAR with BK eyes showing a significantly higher improvement (p<0.05) compared to FD eyes. The only factor showing a significant correlation (p<0.05) with visual acuity enhancement was the implant of a lenticule thinner than 100 m. Recipient features significantly (p<0.05) associated with complications observed after surgery were glaucoma and diabetes mellitus. Conclusion: The use of a graft thinner than 100 m can provide better visual acuity recovery while recipients affected by glaucoma or diabetes mellitus are more prone to develop complications after surgery.